The Influence of Zakat Assistance on Academic Achievement Among University Students in Malaysia and Indonesia: A Pilot Study - Yahaya, Salimah; Awang, Azarudin; Ngah, Nazlin Emieza; Salma Musfiroh, Mila Fursiana; Bashori, Akmal (Information Management and Business Review, 2024)
It is well known that knowledge and education are the best solutions to abolish the Asnaf people from poverty. As a result, zakat institutions actively play an essential role in distributing zakat funds through educational assistance to the asnaf groups in Malaysia and Indonesia. This measure ensures that the asnaf groups receive educational opportunities and succeed like others. Dropping out of studies due to failure to pay tuition fees is among the issues that are often reported in most past studies. Therefore, this study was conducted to identify and analyze the influence of zakat assistance on the academic achievement of students at Universiti Teknologi MARA Terengganu Branch, Malaysia (UiTMCT) and Universitas Sains Al-Qur’an, Indonesia (UNSIQ). This study also provides recommendations to empower zakat assistance at UiTMCT and UNSIQ. This study used a quantitative research method involving data collection by distributing questionnaires to 54 students at UiTMCT and UNSIQ. The findings were analyzed using the Statistical Package for Social Science (SPSS) software (version 24). The t-test results showed a significant difference in academic performance and governance between UiTMCT and UNSIQ, with a p-value of less than 0.05. This study is anticipated to provide insight to the community on the efforts to empower zakat institutions to assist asnaf fisabilillah in higher education institutions (IPTs) in Malaysia and Indonesia.